PENGARUH PELATIHAN DAN PENGEMBANGAN TERHADAP KINERJA DRIVER PT GO-JEK MALANG - Mukhammad fatkurrozi; Pardiman Pardiman; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to find out about how the performance evaluation of PT Go-Jek driver services in Malang City. In this study, the variable used to measure performance appraisal is to use an analysis of the effects of training and development. Based on data available at PT Go-Jek's Office, there are 10,000 drivers spread across Malang City. And from the total, there are only 99 drivers who meet the criteria or qualify as a research sample. In determining this sample, the researcher uses the slovin formula method, which is the determination of the sample using a certain formula. There is also the analytical technique used, namely multiple linear regression analysis. From this study, it was found that the training variables had a positive and significant effect on performance appraisal of PT Go-Jek Malang drivers. Similarly, the development variable, also has the same effect that is positive and significant effect on performance evaluation on the driver of PT Go-Jek Malang. As well as the effects simultaneously or together, these two variables show the results that training and development simultaneously have a significant effect on performance appraisal of PT Go-Jek drivers in Malang City Keywords : Online Transportation, Driver Performance Evaluation, Analysis of Training and Development Effects.